2022
DOI: 10.3389/fmicb.2022.810746
|View full text |Cite
|
Sign up to set email alerts
|

Oregano Oil and Harmless Blue Light to Synergistically Inactivate Multidrug-Resistant Pseudomonas aeruginosa

Abstract: Blue light (BL) at 405 nm and oregano essential oil (OEO) have shown bactericidal activity by its own. Here, we demonstrated that the two synergistically killed multidrug-resistant (MDR) Pseudomonas aeruginosa (Pa). Pa ATCC19660 and HS0065 planktonic cells and mature biofilms were reduced by more than 7 log10 after treatment by BL combined with OEO, in sharp contrast to no significant bacterial reduction with the monotreatment. The duo also sufficiently eliminated acute or biofilm-associated infection of open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Their inhibitory activity against all bacteria tested is similar to Amoxicillin-Clavulanic acid. Our results were similar to those obtained in other studies, which confirm both activities (antibacterial and antibiofilm) on S. aureus [80], E. coli [81], and P. aeruginosa [82,83].…”
supporting
confidence: 92%
“…Their inhibitory activity against all bacteria tested is similar to Amoxicillin-Clavulanic acid. Our results were similar to those obtained in other studies, which confirm both activities (antibacterial and antibiofilm) on S. aureus [80], E. coli [81], and P. aeruginosa [82,83].…”
supporting
confidence: 92%
“…27 Blue light as an efficient bactericidal means is supported by wealth of literature regardless of drug resistance. 50,51 Therefore, blue light, as opposed to UV light, is recommended to be applied in phenolic compound-based POT. Besides, phenolic compounds, which are extracted from natural compounds, exhibit better biocompatibility and bioavailability compared to synthetic pharmaceuticals.…”
Section: A Cascade Phototoxic Reaction Triggered By Phenolic Compound...mentioning
confidence: 99%
“…It would be more rational to apply UV light for food decontamination, not for clinics. ,, On the contrary, blue light is highly biocompatible and holds great potential for clinical practices . Blue light as an efficient bactericidal means is supported by wealth of literature regardless of drug resistance. , Therefore, blue light, as opposed to UV light, is recommended to be applied in phenolic compound-based POT.…”
Section: A Cascade Phototoxic Reaction Triggered By Phenolic Compound...mentioning
confidence: 99%
“…An examination of the ingredients of oregano EO, together with microbiological tests, revealed that carvacrol and its isomer thymol are the primary phytochemicals that work together with BL to achieve synergistic killing. This research provides compelling evidence for the use of carvacrol and thymol as helpful benchmarks in evaluating and establishing the antibacterial effectiveness of different oregano EO products ( Lu et al, 2022a ). Therefore, as mentioned, in addition to the use of a thymol-based drug platform, the combined use of BL and thymol could be a promising antibiofilm approach for managing P. aeruginosa infections; however, more confirmatory studies are needed in this field.…”
Section: Thymolmentioning
confidence: 99%